Avaliação de eritropoietina humana recombinante por métodos cromatográficos validados e correlação com o bioensaio - Ferretto, Ricardo Machado (2009)
Erythropoietin is a endogenous glycoprotein which stimulates the erythropoiesis. Clinically is used for the treatment of renal anaemia. The chromatographic method for the potency evaluation of recombinant human erythropoietin (rhEPO) in pharmaceutical products was validated in the present work. A size-exclusion liquid chromatography method (SE-LC) was validated using a BioSep-SEC-S 2000 column (300 mm x 7,8 mm I.D.), maintained at ambient temperature (25°C). The mobile phase consisted of 0.001 M monobasic potassium phosphate, 0.008 M dibasic sodium phosphate and 0.2 M sodium chloride buffer, pH 7.4, run isocratically at a flow rate of 0.5 mL/min with detection at 214 nm. The chromatographic separation was obtained within 30 min and it was linear in the concentration range of 5-150 μg/mL (r2=0.9991). Validation parameters were evaluated such as sensitivity, precision, accuracy, detection limit, quantitation limit and robustness. The specificity was evaluated by the peak purity of the Recombinant Human Erythropoietin Biological Reference Preparation of European Pharmacopoeia (rhEPO-SBR) storage under stress conditions. The proposed method was applied for the analysis of erythropoietin in pharmaceutical products, evaluating also the dimmers and high-molecular-mass forms. Moreover, was performed the analysis of erythropoietin by reversedphase liquid chromatography (RP-LC), evaluating the sulphoxides and deamidates forms. The correlation with the methods was established, showing mean differences between the estimated potencies of 2.50% lower for the bioassay, and 9.29% higher for the RP-LC, compared with the sizeexclusion liquid chromatography method, with significative correlation, conform calculated for the Pearson s correlation coefficient (r=0,9629 e r=0,9422, respectively). The alternative established represents a contribution towards the reduction or replacement of the animals improving the quality control and assuring the safety and efficacy of the biological product.